Identification of Salmonella Enteritidis and Salmonella Typhimurium in guinea pigs by the multiplex PCR - Marcelo M., Geraldine (2017)
The aim of this study was to identify by mutiplex PCR-based assays the possible presence of serovars Salmonella Typhimurium and Enteritidis in 25 strains of Samonella spp that were previously isolated from guinea pigs and identified by their metabolic characteristics. The molecular analysis identified all 25 strains as Salmonella Typhimurium, evidencing the primer amplification of genes invA and fliC of Salmonella spp and Salmonella Typhimurium, respectively. This study established a rapid methodology for molecular identification of Salmonella Typhimurium and Enteritidis isolated from guinea pigs.